DESIGN AND IMPLEMENTATION OF PRIVACY PRESERVING SECURE SCHEMES FOR BIOMETRIC TEMPLATES - SADHYA, DEBANJAN (iit bhu varanasi, 2016)
Biometrics based aut hentication systems have garnered widespread popularity due to their various ac\vantages over contemporary token based systems. The core of a typical biometric framework consists of a database wherein the biometric data of the registered users get. stored. This database can either be stored locally ( e.g. in smart cards), or in a centralized manner ( e.g. servers). From a security point of view, the risks associated with such databases are alarmingly high. Theoretically, they can be subjecte<l to a wide variety of external attacks by an adversary, thereby compromising both the security and privacy aspects of the users. Some primary examples of these user predicaments include unauthorized access, privacy breach and even identity theft iu t he worst case. Considering the fact that biometric entries are mostly invariant with time, (i.e. they cannot be re-issued like passwords on being compromised) the stakes for protecting these unique entries become much higher.
This thesis submitted by IIT BHU Varanasi, Phd scholar and supervised by Dr. Sanjay Kumar Singh
Keywords: BIOMETRIC TEMPLATES; DESIGN AND IMPLEMENTATION